Targeted Sanctions: a Tool of Foreign Policy, Unfair Competition or Global Social Engineering? - L. L. Fituni (Vestnik MGIMO-Universiteta)
Through the recent decades, the use of asymmetric and hybrid measures in international relations has acquired a qualitatively new scale and system. Today such measures have turned into one of the leading forms of external pressure and subsequent coercion, often exceeding the effectiveness of such straightforward instruments as the threat of potential use of force and almost equal to real power actions. Arguably, among those asymmetric and hybrid measures, Western countries assign a key role to the pressure of international sanction upon competitor nations and uncooperative actors on the world arena. The article is devoted to a critical analysis of some common approaches to the study of the problems of «targeted» sanctions in the theory and practice of international relations and the use of sanctions as a means of achieving geostrategic objectives, including such ambitious ones as social constructivism and social engineering on national, regional and global scales. Particular attention is paid to the contribution of Thomas Biersteker to the development of the theory and of practical designs of «targeted sanctions» in international relations. The author disputes with him over some issues related to the effectiveness of targeted sanctions and the impact they produce upon various sectors of the targeted societies. Based on the author’s schematic matrix of sanctional influences upon national elites and possible limits of their responses, the article formulates the principles of segmentation of the national elites both for the purposes of identifying the layers most susceptible to sanctional pressure and singling out most effective and capable strata from the point of view of practical implementation of the indented outcomes of the undertaken pressure from the outside.